Розвиток ідеології розробки калібровок інструменту для холодної прокатки труб зі сплавів на основі титану - Міщенко, О.В. (Physico-technological Institute of Metals and Alloys, 2023)
The article is devoted to the issues of calibration and durability of the deforming tool of cold rolling tube mill (CRTM) in the production of titanium alloy pipes. The state and tendencies of methods of construction of calibrations for cold rolling of pipes from alloys based on titanium are analyzed. The main types of calibrations, their advantages and disadvantages, as well as the tasks that are set before modern calibrations are considered. Conclusions and recommendations directly related to improving the quality of cold-rolled pipes made of titanium alloys by increasing the accuracy of their dimensions are noted. The data on the influence of the size of the camber on the accuracy of rolled pipes in the CRTM was analyzed. The analysis compared calibrations based on the cross-sectional geometry of the Cassini ellipse and oval. The highlighted advantages of Cassini oval will improve the accuracy of the cross-section of rolled pipes and provide many opportunities for the distribution of crimps in the design of calibrations. This allows the Cassini oval to be recommended for use as a cross-sectional profile of calibres. The relevance of closed solutions in the qualitative analysis of the influence of the planned technological regimes of the cold rolling process of pipes on the choice of the width of the gauges is considered. The investigation of the dependence of the volume of rolled tubes from titanium alloys from wear calibres CRTM was carried out. Dependences of wear resistance of gauge on volumes of rolled pipes from titanium alloys are defined that showed the evident influence of the chemical composition of the material of gauges on their wear resistance during work. The results obtained in the course of the research allowed us to represent a number of important conclusions on the possibility of developing methods for constructing calibrations of working tools of CRTM and to suggest recommendations for improving the wear resistance of calibres during cold rolling of titaniumbased alloy pipes.